Radiolabeled cCPE peptides for SPECT imaging of claudin-4 overexpression in pancreatic cancer - Baguna-Torres, J; Mosley, M; Koustoulidou, S; Hopkins, S; Knapp, S; Chaikuad, A; Kondoh, M; Tachibana, K; Kersemans, V; Cornelissen, B (Society of Nuclear Medicine, 2020)
Introduction: Overexpression of tight junction protein claudin-4 has been detected in primary and metastatic pancreatic cancer tissue, and is associated with better prognosis in patients. Non-invasive measurement of claudin-4 expression by imaging methods could provide a means for accelerating detection and stratifying patients into risk groups. Clostridium perfringens enterotoxin (CPE) is a natural ligand for claudin-4 and holds potential as a targeting vector for molecular imaging of claudin-4 overexpression. A glutathione S-transferases (GST)-tagged version of the C-terminus of CPE (cCPE) was previously used to delineate claudin-4 overexpression by single photon emission computed tomography (SPECT), but showed modest binding affinity and slow blood clearance in vivo.